Problems and Measures in the Transformation and Development of P2P Online Lending Platforms in Hebei Province under the Background of Big Data--Based on the Perspective of the Difference among Beijing, Shanghai and Guangzhou - Xiwen Li, Fang Chen, Xiaodan Jiang (Forest Chemicals Review, 1970)
In the big data era, the openness and sharing of data provides opportunities for the development of P2P online lending platforms. P2P online lending platforms have become an important financing channel for small, medium and micro enterprises. However, due to economic, geographic, historical and other factors, there is still a big gap in the development of platforms in various regions. Based on the analysis of the differences among P2P online lending platforms in Hebei Province, Beijing, Shanghai and Guangzhou, it is found that there are some problems in the P2P online lending platforms in Hebei Province, such as weak foundation, insufficient supervision, low recognition, poor industry development environment and low talent support. Therefore, in order to promote the platform transformation and high-quality development, this paper proposes that not only the relevant departments need to innovate the cooperation mechanism, improve the laws and policies system, and strengthen the industry management, but also need to vigorously consolidate the foundation and enhance the connotation of the P2P online lending platforms from the aspects of strategic planning and talent training.